THE EFFECT OF CURRENT RATIO, DEBT TO ASSETS RATIO AND WORKING CAPITAL TURNOVER ON RETURN ON ASSSETS IN PLASTIC COMPANIES AND PACKING LISTED ON INDONESIA STOCK EXCHANGE - Kurniawan Gultom, Dedek; Datuk, Bahril; Indriani, Mei (RADJA PUBLIKA, 2021)
This research was conducted with the aim of knowing the effect of the Current Ratio, Debt to Assets Ratio and Working Capital Turnoveron Return On Assets in plastic and packaging companies listed on the Indonesia Stock Exchange. The population in this study is all plastic and packaging company listed on the Indonesia Stock Exchange while the sample that meets the criteria for sampling observations carried out for seven years and as many as six yearsplastic and packaging company listed on the Indonesia Stock Exchange. This research approach uses associative research.Data collection techniques in this study using documentation techniques. cand the analysis technique used is multiple linear regression analysis, hypothesis testing and coefficient of determination. The results showed that the independent variables in this study had a simultaneous effect on Return On Assets. While the partial test proves the Cuirrent Ratio variable has a significant effect on Return On Assets, while partially proves the Debt to Assets Ratio variable andWorking Capital Turnover does not have a positive effect on Return On Assets in plastic and packaging companies listed on the Indonesia Stock Exchange.